A Study on Influence of Finger-Shaped Milling Tool Offsets on Machining Accuracy of Vacuum Pump Screw Rotors
Chapter 1. Introduction; Chapter 2. Mathematical model for generation of finger-shaped cutting tool and rotor profiles; Chapter 3. Application of sensitivity matrix and SVD method on rotor milling; ...